Determining the Relation between Turkish MiddleSchool Students’ Internet Addiction and Perceived Social Support from Family - Işık, Işıl; Ergün, Gül (Addicta: The Turkish Journal on Addictions, 2018)
The purpose of this study is to determine the relation between middle-school students’ Internet Addiction levels and their perceived social support from family. The study has been conducted in the cross-sectional descriptive design, and data were collected from 3,391 students in the 5th-8th grades at 23 middle schools under the Directorate of National Education in the city of Burdur and its central villages. A personal information form, the Internet Addiction Scale, and the Social Support Received from the Family Scale have been used for collecting data. After making the necessary explanations to the students, an informed consent form was sent to their parents/legal guardians; students who returned these forms were included in the study. The quantities, percentages, averages, and standard deviations, which are among descriptive statistical methods, have been used in evaluating the data. Pearson’s correlation and regression analysis were applied over the study’s continuous variables. Of the students in the study, 4.6% were observed to have Internet addiction at a pathological level. The factors influencing Internet addiction have been determined as: lack of social support received from family, being male, low school success, having a high weekly allowance, being in higher grades, and being online frequently. The rate of internet addiction is higher in this group and found to relate to the perceived support from family To